Classical recording : a practical guide in the Decca tradition - Haigh, Caroline; Dunkerley, John; Rogers, Mark (Sound engineer); Audio Engineering Society (Routledge Taylor & Francis Group, 2021)
"Classical Recording: A Practical Guide in the Decca Tradition is the authoritative guide to all aspects of recording acoustic classical music. Offering detailed descriptions, diagrams and photographs of fundamental recording techniques such as the Decca tree, this book offers a comprehensive overview of the essential skills involved in successfully producing a classical recording. Written by engineers with years of experience working for Decca, Abbey Road Studios and as freelancers, Classical Recording equips the student, the interested amateur and the practising professional with the required knowledge and confidence to tackle everything from solo piano to opera"--
Keywords: Decca Music Group; Sound -- Recording and reproducing; Music